Free and Bound Phenolic Profiles of Rosa roxburghii Tratt Leaves and Their Antioxidant and Inhibitory Effects on α-Glucosidase - Yang, Yuzhe; Li, Wu; Xian, Wenyan; Huang, Wei; Yang, Ruili (Frontiers in Nutrition, 2022)
Rosa roxburghii Tratt (R. roxburghii) tea is a traditional Chinese beverage. This study aims to investigate and compare the phenolics in free and bound forms of two cultivars of R. roxburghii leaves, and their bioactivities. The total phenolic content of free and bound fractions was 72.71 and 17.75 mg GAE/g DW in Gui Nong No. 5 (GNN5) and 94.28 and 11.19 mg GAE/g DW in Seedless Cili (SC). A total of 37 phenolic compounds were characterized and quantified by UPLC-Q-Exactive Orbitrap/MS with ellagic acid, quercitrin, isoquercitrin, and quininic acid in free fraction, while gallic acid, ellagic acid, and hyperoside were main compounds in bound fraction. The free fraction with higher phenolic contents also showed excellent performances on antioxidant activities and α-glucosidase inhibitory potency than bound phenolics. Therefore, the results highlight that R. roxburghii leaves are a promising source enriched in phenolic constituents for functional beverages and nutritional foods.